Combined presence of multiple gastrointestinal stromal tumors along with duodenal submucosal somatostatinoma in a patient with neurofibromatosis type 1 - Tarun Kumar; Brijnandan Gupta; Prasenjit Das; Deepali Jain; Hemant Ashok Jain; Kumble S Madhusudhan; Nihar Ranjan Dash; Siddhartha Datta Gupta (Wolters Kluwer Medknow Publications, 2016)
Neurofibromatosis type-1 (NF-1) is an autosomal dominant disorder, with increased risk of developing benign and malignant tumors of the gastrointestinal tract (GIT). However, the synchronous presence of multiple GIT stromal tumors and duodenal submucosal somatostatinoma, like in this 50-year-old female NF-1 patient, is very rare. She presented with hematemesis, malena, along with multiple neurofibromas all over the body. Thorough radiological and peroperative work-up revealed multiple ulcerated submucosal and serosal nodules in the proximal small intestine. Histological work-up revealed diagnosis of a duodenal submucosal somatostatinoma with multifocal serosal gastrointestinal stromal tumors. This case is being reported to highlight the rare coincidence of multiple GIT tumors in an NF-1 patient.